2021
DOI: 10.3390/su13042212
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Well-Being in Urban Wilderness: Assessing States of Calmness and Alertness in Informal Green Spaces (IGSs) with Muse—Portable EEG Headband

Abstract: In this experiment, we operated within the novel research area of Informal Green Spaces (often called green wastelands), exploring emotional well-being with the employment of portable electroencephalography (EEG) devices. The apparatus (commercial EEG Muse headband) provided an opportunity to analyze states of calmness and alertness in n = 20 participants as they visited selected Informal Green Spaces in Warsaw, Poland. The article aims to test the hypothesis that passive recreation in Informal Green Spaces (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…They found that the natural views triggered lower levels of oxy-Hb concentration and increased oxy-Hb when viewing urban busy scenes in the healthy adult population and associated the lower oxy-Hb with restorative effect ( 11 , 73 ) and reduced rumination ( 74 ). It has been shown that scenes of nature require less cognitive resources and less strenuous attention ( 75 , 76 ) when compared to busy urban scenes abundant with elements of infrastructure, cars, buildings, and crowds, and our findings seem to support this general premise. When it comes to the differences between the groups, results indicated the marginally significant effect of site * group ( p = 0.06), showing the trend of patterns of brain oxidation in Clinical being different to those observed in the Healthy group.…”
Section: Discussionsupporting
confidence: 81%
“…They found that the natural views triggered lower levels of oxy-Hb concentration and increased oxy-Hb when viewing urban busy scenes in the healthy adult population and associated the lower oxy-Hb with restorative effect ( 11 , 73 ) and reduced rumination ( 74 ). It has been shown that scenes of nature require less cognitive resources and less strenuous attention ( 75 , 76 ) when compared to busy urban scenes abundant with elements of infrastructure, cars, buildings, and crowds, and our findings seem to support this general premise. When it comes to the differences between the groups, results indicated the marginally significant effect of site * group ( p = 0.06), showing the trend of patterns of brain oxidation in Clinical being different to those observed in the Healthy group.…”
Section: Discussionsupporting
confidence: 81%
“…Besides some benefits associated to certain type of environmental typologies, it has been debated whether the quality of the urban green space could disparately affect individual brain responses. To address this, Herman et al ( 92 ) compared passive recreation in informal green spaces (i.e., patches of vegetated areas scattered throughout the city which are not included in the city’s planning documents as green spaces, but provide numerous benefits to residents, including walking paths and pet areas, recreational spaces, urban agriculture lots) against traditional urban green spaces (e.g., city parks recognized or planned for recreational use by inhabitants)–in terms of well-being perception and portable EEG activity. No significant differences were observed–for frontal alpha, beta, delta, gamma, or theta oscillations–between the two exposure types.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the results of full spectral power and alpha-beta-gamma spectral power, the proposed algorithm can determine whether a person has IA through EEG signals in the absence of biomarkers. In addition, the results show that the proposed algorithm has obvious advantages in processing raw data, which can reduce the diagnosis time and have the potential to be used in some real-time health monitoring systems [28][29][30].…”
Section: Introductionmentioning
confidence: 99%